2019
DOI: 10.7759/cureus.6107
|View full text |Cite
|
Sign up to set email alerts
|

Resident Knowledge and Perception of Pain Management

Abstract: Chronic pain involves a complex mechanism that afflicts 50 million adults in the United States and incurs societal costs upwards of $560 billion annually. The consequences of this epidemic have resulted in an epidemic of its own, with the opioid crisis becoming a top priority in healthcare. Historically, the sub-optimal practices of overprescribing opioids and inadequate monitoring of iatrogenic addiction have contributed to this problem. If progress is to be made in this area, it is imperative that we examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…According to the findings in our study, a case-based, interactive online educational module is an effective intervention for improving student knowledge, attitudes, and perceived competence regarding OPM concepts. Prior to our educational intervention, students reflected levels of uncertainty surrounding OP and PM concepts comparable to those observed in similar peer groups [ 11 , 12 ]. However, posttest results indicated overall student improvement in key knowledge areas such as opioid-sparing PM strategies (alternative medications, first-line treatments for specific pain types), opioid stewardship (PDMP utilization, proper opioid disposal), the opioid epidemic (prescriber contribution, opioid diversion, risk factors for opioid misuse), and appropriate opioid management and prescribing (recommended guidelines, opioid tapering, MME conversions, management of special populations).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…According to the findings in our study, a case-based, interactive online educational module is an effective intervention for improving student knowledge, attitudes, and perceived competence regarding OPM concepts. Prior to our educational intervention, students reflected levels of uncertainty surrounding OP and PM concepts comparable to those observed in similar peer groups [ 11 , 12 ]. However, posttest results indicated overall student improvement in key knowledge areas such as opioid-sparing PM strategies (alternative medications, first-line treatments for specific pain types), opioid stewardship (PDMP utilization, proper opioid disposal), the opioid epidemic (prescriber contribution, opioid diversion, risk factors for opioid misuse), and appropriate opioid management and prescribing (recommended guidelines, opioid tapering, MME conversions, management of special populations).…”
Section: Discussionmentioning
confidence: 96%
“…Importantly, this inadequate preparation of medical students does not change at graduation, but rather traverses their transition into residency where knowledge deficits may have greater consequences. Garcia et al [ 11 ] administered a survey to assess opioid knowledge and medical school preparation to first-year internal medicine residents following orientation and found that residents scored an overall 60.7% on opioid knowledge concepts. Furthermore, less than 50% of these residents felt that their medical school curricula had sufficiently prepared them for managing patient pain, and 90% felt inadequately prepared to dose opioids for patients or understand state and federal OP requirements [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect unfamiliarity of surgical, medical, and anesthesia care teams with effectively managing acute pain needs in chronic pain patients receiving intrathecal analgesics. 32,33 Nearly 40% of consultations were placed reflexively due to the presence of an IDDS. Remaining consults were placed for assistance in optimizing acute on chronic pain.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%
“…Accordingly, residents across all medical disciplines are often underprepared to prescribe opioids for patient pain or respond to various opioid-related patient management scenarios [ 9 - 11 ]. The magnitude of this deficit is well-exemplified in a recent study surveying surgical residents at a large academic institution: 90% reported no formal training in best practices of pain management or opioid prescribing, despite reliance on opioids for postoperative pain management [ 11 ].…”
Section: Introductionmentioning
confidence: 99%